The Effectiveness of Problem-Based Learning in Classroom Guidance to Reduce Bullying at Jepon State Junior High School 1 - Lela Candra Ayu Agustina; Siti Fitriana; Farikha Wahyu Lestari (Jurnal Counseling Care, 2025)
AbstractThis study examines the effectiveness of ProblemBased Learning (PBL) method in classroom guidance services to reduce bullying behavior at SMP Negeri 1 Jepon. The background of this research is the high number of verbal bullying cases among eighth-grade students. This research used a quantitative approach with a pre-experimental design (one group pretest-posttest). The research sample consisted of 20 students who showed a high tendency of bullying behavior. Data were collected through bullying behavior questionnaires, observation, and interviews. The results of the analysis showed a significant decrease in the average bullying score after the PBL service was provided. This proves that the application of the PBL method in classroom guidance is effective in reducing bullying behavior. This study recommends the structured implementation of PBL-based classroom guidance services as an innovative alternative in bullying prevention at school. Keywords: Problem Based Learning, classroom guidance, bullying